The function of bacterial HtrA is evolutionally conserved in mammalian HtrA2/Omi. - Chung, H.J.; Jamal, M.A.H.M.; Hong, S.T. (Scientific reports, 2020)
Although the malfunction of HtrA2/Omi leads to Parkinson's disease (PD), the underlying mechanism has remained unknown. Here, we showed that HtrA2/Omi specifically removed oligomeric ?-Syn but not monomeric ?-Syn to protect oligomeric ?-Syn-induced neurodegeneration. Experiments using mnd2 mice indicated that HtrA2/Omi degraded oligomeric ?-Syn specifically without affecting monomers. Transgenic Drosophila melanogaster experiments of the co-expression ?-Syn and HtrA2/Omi and expression of genes individually also confirmed that pan-neuronal expression of HtrA2/Omi completely rescued Parkinsonism in the ?-Syn-induced PD Drosophila model by specifically removing oligomeric ?-Syn. HtrA2/Omi maintained the health and integrity of the brain and extended the life span of transgenic flies. Because HtrA2/Omi specifically degraded oligomeric ?-Syn, co-expression of HtrA2/Omi and ?-Syn in Drosophila eye maintained a healthy retina, while the expression of ?-Syn induced retinal degeneration. This work showed that the bacterial function of HtrA to degrade toxic misfolded proteins is evolutionarily conserved in mammalian brains as HtrA2/Omi.